Therapeutic Insights in Chronic Kidney Disease Progression - Shabaka, Amir; Cases-Corona, Clara; Fernandez-Juarez, Gema (Frontiers in Medicine, 2021)
Chronic kidney disease (CKD) has been recognized as a leading public health problem worldwide. Through its effect on cardiovascular risk and end-stage kidney disease, CKD directly affects the global burden of morbidity and mortality. Classical optimal management of CKD includes blood pressure control, treatment of albuminuria with angiotensin-converting enzyme inhibitors or angiotensin II receptor blockers, avoidance of potential nephrotoxins and obesity, drug dosing adjustments, and cardiovascular risk reduction. Diabetes might account for more than half of CKD burden, and obesity is the most important prompted factor for this disease. New antihyperglycemic drugs, such as sodium-glucose-cotransporter 2 inhibitors have shown to slow the decline of GFR, bringing additional benefit in weight reduction, cardiovascular, and other kidney outcomes. On the other hand, a new generation of non-steroidal mineralocorticoid receptor antagonist has recently been developed to obtain a selective receptor inhibition reducing side effects like hyperkalemia and thereby making the drugs suitable for administration to CKD patients. Moreover, two new potassium-lowering therapies have shown to improve tolerance, allowing for higher dosage of renin-angiotensin system inhibitors and therefore enhancing their nephroprotective effect. Regardless of its cause, CKD is characterized by reduced renal regeneration capacity, microvascular damage, oxidative stress and inflammation, resulting in fibrosis and progressive, and irreversible nephron loss. Therefore, a holistic approach should be taken targeting the diverse processes and biological contexts that are associated with CKD progression. To date, therapeutic interventions when tubulointerstitial fibrosis is already established have proved to be insufficient, thus research effort should focus on unraveling early disease mechanisms. An array of novel therapeutic approaches targeting epigenetic regulators are now undergoing phase II or phase III trials and might provide a simultaneous regulatory activity that coordinately regulate different aspects of CKD progression.